The effect of management response similarity on online hotel booking: Field evidence from Expedia. Issue 7 (18th June 2019) - Zhang, Zili; Li, Hengyun; Meng, Fang; Li, Yuanshuo
Abstract : Purpose: This paper aims to examine the influences of the number of hotel management responses and especially the textual similarity in hotel management responses to online reviews on hotel online booking. Design/methodology/approach: This study used the data from 437 hotels in New York City on Expedia. The data specifically include online reviews, management responses and real-time number of online hotel bookings, which were merged to create one dataset for this study. To calculate the management response similarity, three widely recognized text mining functions of calculating textual similarity were adopted in this model. Fixed-effect panel data model was then used to examine the influence of management response to consumer online reviews on online hotel booking volume. Findings: The empirical results demonstrate that the number of management responses to consumer online reviews does not significantly affect hotel booking; compared to none or only one management response, or management responses with low similarity, management responses with high similarity can significantly reduce the hotel booking on Expedia. Practical implications: This study suggests that the similarity of management responses influences customers' hotel booking, and hotel managers should avoid providing too similar management responses. Originality/value: First, this study, for the first time, proposes the concept of management response similarity and its measurement methods. Second, this study takes an initial attempt to empirically test the influence of response similarity on hotel booking by using secondary data online.